An investigation into the quality of life of beneficiaries post Extended Public Works Programmes (EPWP's) participation in the City of Tshwane (CoT) region 2: Gauteng : a case of New Eersterust - Mokoena, David Ndethe (University of Limpopo, 2017)
This qualitative case study investigates the relevance of the Extended Public Works Programme (EPWP) as a solution to unemployment and poverty. A qualitative case study research design was used to collect and analyse the data. Data collection instruments consisted of interviews, questionnaires, observations and document analysis. Data analysis was largely in the form of thematic approach, since the study was qualitative. The choice of a qualitative design was informed by the need to engage the beneficiaries in their lived experiences during and after participating in the EPWPs. The main findings of the study were that although the EPWP improves the quality of life of the beneficiaries, however, it is not a sustainable solution to unemployment and poverty. That is because the structural constraints which confront beneficiaries at the end of the EPWP remain an obstacle to them in terms of employment opportunities and self-employment. The study therefore recommends a more integrated approach to the problem. It is recommended that the government develops a post EPWP sustainability plan which incorporates infrastructural and social development issues in all projects. Key words Poverty, EPWP, Unemployment, Work, Decent work, Productive work, Quality of Life Development and Developmental state.
Thesis (M. Dev. (Planning and Development)) -- University of Limpopo, 2017
Keywords: Poverty; EPWP; Unemployment; Work; Decent work; Productive work; Quality of life; Development and Developmental State; Public works; Economic assistance, Domestic; Employment stabilization; Unemployment -- South Africa -- Gauteng